Transcriptomic Profiling of Circular RNAs in the Goat Rumen During Fetal and Prepubertal Period - Zhong, Tao; Wang, Cheng; Wang, Meng; Zhan, Siyuan; Freitas-de-Melo, Aline; Wang, Linjie; Cao, Jiaxue; Dai, Dinghui; Guo, Jiazhong; Li, Li; Zhang, Hongping; Niu, Lili (Frontiers in Physiology, 2022)
Circular RNAs (circRNAs) are key regulatory factors with vital functions in various biological activities. However, little has been reported concerning the genetic regulation of circRNAs during rumen development in goats. The aim of this study was to identify the genome-wide expression profiles of circRNAs in the rumen of goats during fetal development and before and after weaning. Histological morphology showed that from the fetal period (days 60 and 135 of gestation) to the prepuberal period (days 60 and 150 of age) the rumen papilla developed gradually, and the thickness of the rumen muscular layer increased. A total of 11,149 circRNAs were identified in the four development stages by RNA-sequencing. From this, 1,518 were differentially expressed circRNAs (DECs). Fifty-eight DECs were up-regulated from 60 to 135 days of gestation, and 93 from day 135 of pregnancy to 30 days after birth. A large proportion (598) of DECs were down-regulated from day 135 of gestation to 30 days after birth. The expression levels of six randomly selected circRNAs were validated by qPCR, and their back-splicing junction (BSJ) sites were also confirmed. Ontology and pathway analyses revealed that the parental genes of DECs were mainly involved in the signaling pathways related to cell proliferation and apoptosis. The interaction network of circRNAs with their target miRNAs showed its involvement in cell proliferation and apoptosis signaling pathways. In conclusion, we identified the genome-wide expression profiles of circRNAs in the rumen of goats during fetal development and before and after weaning. These results provide a basis for further study on the regulatory effect of circRNAs on the development of rumen tissues.